2015
DOI: 10.1016/s1995-7645(14)60330-8
|View full text |Cite
|
Sign up to set email alerts
|

Monascus pilosus-fermented black soybean inhibits lipid accumulation in adipocytes and in high-fat diet-induced obese mice

Abstract: These results suggest that the anti-obesity effects of MFBS are elicited by regulating the expression of adipogenesis-related genes in adipocytes and WAT of HFD-induced obese mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Yang et al [40] demonstrated that weight loss herbal intervention therapy (W-LHIT) reduced body weight, without suppression of appetite, in obese mice, by significantly increasing the gene expression of Pparg (peroxisome proliferator activated receptor gamma) and Fabp4 (fatty acid binding protein 4) epdidymal fat tissues. In contrast, Lee et al [41] Monascus pilosus-fermented black soybean inhibits lipid accumulation in adipocytes and in high-fat diet-induced obese mice, but significantly lower gene expression of adipogenesis-related genes like peroxisome proliferator-activated receptor gamma (Pparg) and fatty acid-binding protein 4 (Fabp4). Kim et al [42] showed that anti-obesity effect of Solidago virgaaurea extract in high-fat diet-fed SD rat was associated with decreased acetyl-CoA carboxylase, fatty acid synthase, and Fabp4.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [40] demonstrated that weight loss herbal intervention therapy (W-LHIT) reduced body weight, without suppression of appetite, in obese mice, by significantly increasing the gene expression of Pparg (peroxisome proliferator activated receptor gamma) and Fabp4 (fatty acid binding protein 4) epdidymal fat tissues. In contrast, Lee et al [41] Monascus pilosus-fermented black soybean inhibits lipid accumulation in adipocytes and in high-fat diet-induced obese mice, but significantly lower gene expression of adipogenesis-related genes like peroxisome proliferator-activated receptor gamma (Pparg) and fatty acid-binding protein 4 (Fabp4). Kim et al [42] showed that anti-obesity effect of Solidago virgaaurea extract in high-fat diet-fed SD rat was associated with decreased acetyl-CoA carboxylase, fatty acid synthase, and Fabp4.…”
Section: Discussionmentioning
confidence: 99%
“…As well as, significantly suppressed the major signaling transcriptional protein PPARγ, CEBPα, and aP2 expression level. Similar studies have shown that fermented soybean can significantly suppressed the protein level due to the high amount of bioactive ingredients (isoflavones) (Lee et al, ). In our study, we hypothesized that aglycones form of isoflavones and metabolites monacolin K may have anti‐adipogenesis activity by the STAT3/PPARγ/CEBPα signaling pathways.…”
Section: Resultsmentioning
confidence: 71%
“…Previous studies show that fermented soybean hull, Monascus pilosus -fermented black soybean extracts, and Lactobacillus paracasei subsp. paracasei NTU101-fermented tea can reduce the proliferation of 3T3-L1 cells and inhibit lipid accumulation in the 3T3-L1 cell [ 29 , 30 , 31 ]. These results show that fermented plants administration can reduce the proliferation of 3T3-L1 cells and inhibit lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%